2008
DOI: 10.1093/cercor/bhn005
|View full text |Cite
|
Sign up to set email alerts
|

Kinesthetic Imagery and Tool-Specific Modulation of Corticospinal Representations in Expert Tennis Players

Abstract: Specific physical or mental practice may induce short- and long-term neuroplastic changes in the motor system and cause tools to become part of one's own body representation. Athletes who use tools as part of their practice may be an excellent model for assessing the neural correlates of possible bodily representation changes that are specific to extensive practice. We used single-pulse transcranial magnetic stimulation to measure corticospinal excitability in forearm and hand muscles of expert tennis players … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
104
3
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(123 citation statements)
references
References 46 publications
5
104
3
4
Order By: Relevance
“…In their study, Fourkas et al [12] required both expert and novice tennis players to complete the Movement Imagery Questionnaire -revised [MIQ-R; 14]. The amplitude of the motor evoked potential (MEP) resulting from TMS during imagined tennis movements was significantly correlated with the visual and kinaesthetic imagery scores from the MIQ-R in the sample as a whole (r = .52 and .68 respectively), with more vivid imagery scores resulting in greater MEP amplitude.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…In their study, Fourkas et al [12] required both expert and novice tennis players to complete the Movement Imagery Questionnaire -revised [MIQ-R; 14]. The amplitude of the motor evoked potential (MEP) resulting from TMS during imagined tennis movements was significantly correlated with the visual and kinaesthetic imagery scores from the MIQ-R in the sample as a whole (r = .52 and .68 respectively), with more vivid imagery scores resulting in greater MEP amplitude.…”
Section: Introductionmentioning
confidence: 91%
“…Skilled performers also demonstrate significantly higher levels of corticospinal activation following TMS during imagery of movements related to their particular sport, when compared to novice performers [12]. However, these differences dissipate when assessing imagery of more general motor skills, unrelated to their sport [10,12]. It has been demonstrated that intensive physical practice and subsequent improvement in the performance of a motor skill also alters the pattern of neural activation during motor imagery [13], and taken with our knowledge of the imagery ability of elite athletes, this indicates that task experience can influence imagery ability and accompanying neural activation.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…La hipótesis de que las redes neuro-cognitivas son las mismas tanto para los movimientos reales como imaginados podría explicar estos resultados (Fourkas et al, 2008;Kasess et al, 2008;Ramnani, 2006;Stinear et al, (2007).…”
Section: Conclusiones Y Discusiónunclassified
“…Otras investigaciones se han centrado en: la activación de las áreas corticales y subcorticales durante la representación motriz (Fourkas Bonavolontà, Avenanti y Aglioti, 2008;Kasess et al, 2008;Ramnani, 2006); las imágenes motrices en pacientes con lesiones cerebrovasculares (Cicinelli et al, 2006;Sabaté, González y Rodriguez, 2007;Stinear Fleming, Barber y Byblow, 2007); o en paciente con enfermedad de Parkinson (Amick, Schendan, Ganis y Cronin-Golomb, 2006;Helmich, Lange, Bloem y Toni, 2007). En resumen, estos estudios neuronales sobre la representación mental han observado consistentemente que los patrones de activación son comunes tanto a la simulación mental del movimiento como a la generación real del mismo.…”
Section: Introductionunclassified